Analysis of Students’ Difficulties in Reading English Text for EFL Learners in Junior High School - Widy Silva Julianti; Masrupi Masrupi; Yusti Fargianti (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2026)
This study aims to analyze the reading difficulties faced by EFL students at the junior high school level. Using a qualitative descriptive method with content analysis, data were gathered through interviews and classroom observations involving 20 eighth-grade students and one English teacher at SMPN 3 Bantarujeg. The findings show that students experience difficulties in vocabulary mastery, sentence structure comprehension, identifying main ideas, making inferences, and applying reading strategies. In addition, teacher-centered approaches and lack of support from the learning environment contribute to these issues. The study recommends the implementation of strategy-based instruction and supportive classroom practices to improve students’ reading comprehension.